2018
DOI: 10.5530/ijper.52.1.11
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Properties and Protective Effect of Turkish Propolis on t-BHP-Induced Oxidative Stress in Foreskin Fibroblast Cells

Abstract: Objective: Propolis is an important bee product, rich in polyphenolic compounds. It has antitumoral, antioxidant, antimutagenic, and other useful activities. Biological activities of propolis are generally attributed to its substance of polyphenolic compounds. The aim of this study was to investigate the in vitro antioxidant properties and reduction amount of intracellular reactive oxygen species (ROS) in human normal foreskin fibroblast cells by Turkish propolis ethanolic extract (EEP). Method: Total phenolic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 42 publications
1
10
0
Order By: Relevance
“…Figure representthe TPC and TFC in ethanol extracts of propolis reported from various countries, along with a comparison of the findings for BDP (Choi et al, ; Kumazawa et al, ; Laskar et al, ). Most recently, Misir et al () reported the TPC, TFC, and reducing power in ethanol extract of Turkish propolis at 114.07 ± 0.02, 36.02 ± 0.08, and 246.80 ± 0.01 mg per g of sample, respectively. In other studies, Zehra, Yildiz, Şahİn, Asadov, and Kolayli () and Socha, Gałkowska, Bugaj, and Juszczak () investigated the antioxidant properties of propolis from Azerbaijan and Poland, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Figure representthe TPC and TFC in ethanol extracts of propolis reported from various countries, along with a comparison of the findings for BDP (Choi et al, ; Kumazawa et al, ; Laskar et al, ). Most recently, Misir et al () reported the TPC, TFC, and reducing power in ethanol extract of Turkish propolis at 114.07 ± 0.02, 36.02 ± 0.08, and 246.80 ± 0.01 mg per g of sample, respectively. In other studies, Zehra, Yildiz, Şahİn, Asadov, and Kolayli () and Socha, Gałkowska, Bugaj, and Juszczak () investigated the antioxidant properties of propolis from Azerbaijan and Poland, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…It is known that increased oxidative stress causes cell damage and cell death and oxidative stress is among the most important causes of fatal diseases, such as cancer, diabetes, neurodegenerative and cardiovascular diseases (Yalcin et al, 2016). Antioxidant molecules prevent diseases by preventing the formation of free radicals, scavenging the free radicals or repairing the harmful effects of free radicals (Misir et al, 2018). There is no doubt that plants are a good source for biologically active phytochemicals and to date more than 4000 phytochemicals have been identified in plants, including phenolic acid, tannine, coumarin, anthraquinone, flavonoid, phenolic diterpene and anthocyanin subgroups (Mazandarani et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…Different studies have been carried out to determine in vitro the AOA of bee products using biological (cellular) systems. The more recent ones are summarized in Table 6 [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 32 , 33 , 34 , 47 , 74 , 118 , 142 , 161 , 165 , 180 ]. Cell lines of different types and origins have, in the main, been used for this purpose in all bee products.…”
Section: In Vitro Determination Of Aoamentioning
confidence: 99%
“…In vitro and in vivo studies are seldom used to quantify the AOA of bee products, with a wide variability in tests and results, which we will outline below. The antioxidant properties of bee products have been applied to biological systems in vitro and in vivo, e.g., on cell lines [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ], blood cells [ 30 , 31 , 32 , 33 , 34 ], or in different types of diseases in animal models and humans [ 3 , 35 ].…”
Section: Introductionmentioning
confidence: 99%